First-principles Studies of CO2 and NH3 Gas Molecules Adsorbed on Graphene Nanoribbons - Cuong, Nguyen Tien; Tien, Nguyen Manh (VNU Journal of Science: Mathematics - Physics, 2016)
Abstract: We present first-principles studies of CO 2 and NH 3 adsorbed on graphene nanoribbons (GNRs). The electronic and transport properties are calculated based on density functional theory combined with non-equilibrium Green's function method. Absorption energy, density of states, electron density deformation, charge transfer, current-voltage characteristics, and transmission spectra were analyzed. It is found that CO 2 and NH 3 adsorbed on GNRs exhibit acceptor-like and donor-like behaviors, respectively. Both CO 2 and NH 3 molecules show physissorption on GNRs with low adsorption energies and small charge transfers. In other words, the interactions between CO 2 and NH 3 molecules and GRNs are very weak. The results suggest that the sensitivity and selectivity of GRN-based gas sensors could be improved by introducing the dopant, defect, or modification of electronic structures of graphene. Keywords: First-principles, Graphene Nanoribbons, CO2 Adsorbed on Graphene, NH3 Adsorbed on Graphene.